The Influence of Debt Policy, Capital Intensity, and Independent Commissioners on Tax Aggressiveness - Ita Darsita; Salsabilah Azizah (International Journal of Educational and Life Sciences, 2024)
The main objective of the research is to address a knowledge vacuum in the current literature by showing how debt policy, capital intensity, and the existence of independent commissioners influence tax aggressiveness. This study employs a quantitative technique with an associative approach, and it makes use of secondary data. The research subjects in this study are consumer-facing, non-cyclical food and beverage companies that have their stock listed on the Indonesia Stock Exchange from 2019 to 2023. The sample was created by using purposive sampling to exclude fourteen companies. Outliers occurred in 23 samples due to the presence of extreme values during the test. The tool used for data processing is eviews version 10. A partial examination reveals that Capital Intensity influences Tax Aggressiveness, although Debt Policy and Independent Commissioners do not. Identifies the interplay between Tax Aggressiveness and Debt Policy, Capital Intensity, and Independent Commissioners.